The Strength of Electronic Document Evidence in Crime based on Technology and Informataion (Cyber Crime) - Nurkholim Nurkholim (Institute of Computer Science (IOCS), 2020)
The era of globalization has had a very significant impact on human life, the emergence of internet media as a new media has also influenced various fields and sectors in the global order of life. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that as one of the sectors that is also affected by the emergence of information and communication, the legal justice process in Indonesia also adapts to various current developments, the existence of various crimes that are born through internet access or what is commonly referred to as cyber crime, the Indonesian government has made a transformation in dealing with the defendants by issuing various laws and government decisions as one way so that prosecution can be carried out quickly and precisely. involved in the trial process are several electronic documents that are indeed very influential on the judge's decision in the trial process, the presence of such evidence is indeed still a new thing in the judicial process in Indonesia but in reality This has been stated in several articles of the Information Technology and Electronic Law.